Osteology and radiology of the Maned Wolf (Chrysocyon brachyurus) pelvic limb - Siqueira, R. C. [UNESP]; Rahal, S. C. [UNESP]; Inamassu, L. R. [UNESP]; Mamprim, M. J. [UNESP]; Felix, M.; Castilho, M. S. [UNESP]; Mesquita, L. R. [UNESP]; Ribeiro, V. L.; Teixeira, C. R. [UNESP]; Rassy, F. B. (Wiley, 2017)
This study describes the osteology and radiology of the pelvic limb in maned wolves. Ten (five live and five dead) maned wolves (Chrysocyon brachyurus), five males and five females, aged from 2 to 7 years old were used. Digital radiographs were taken and recorded for both pelvic limbs in all animals. Osteology was correlated with the radiographic images. The pelvis had a rectangular shape, and the obturator foramen (foramen obturatum) was oval. The femoral neck (collum femoris) was short and thick. The greater trochanter (trochanter major) extended proximally to near the dorsum of the femoral head (caput ossis femoris). The lateral femoral condyle (condylus lateralis) was larger than the medial condyle (condylus medialis), and the intercondylar fossa (fossa intercondylaris) had a slightly oblique orientation. The proximal tibia displayed medial and lateral condyles with the medial larger. The femur was slightly shorter than the tibia. Seven tarsal bones (ossa tarsi) were present, four long metatarsal bones (ossa metatarsalia II - V) and a short first metatarsal bone (os metatarsal I).
Keywords: anatomy; radiographs; wild animal; wolf